2022
DOI: 10.1080/22221751.2022.2091479
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and genotype-specific disease severity of hepatitis E virus infections in Germany, 2010–2019

Abstract: Zoonotic hepatitis E virus (HEV) is endemic in Europe. Genotype 3 (HEV-3) is predominant but information on subtype distribution, trends and clinical implications in Germany is scarce. We analysed 936 HEV RNA positive samples of human origin and corresponding national surveillance data from 2010 to 2019. Samples were referred to the National Consultant Laboratory and sequenced in at least one of four genomic regions. Sequences were analysed using bioinformatics methods and compared to the latest HEV reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…In addition, both HEV X domain and polyproline region heterogeneity were proposed as being associated with viral persistence ( Lhomme et al, 2014 ). Interestingly, our results show that the HEV-3 X domain has several polymorphic amino acids that are associated with clades, an observation that might be consistent with the recently reported clade differences in clinical behavior ( Schemmerer et al, 2022 ). Additionally, it has recently been suggested that the conserved macrodomain is a potential therapeutic target for coronavirus and alphavirus ( Leung et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, both HEV X domain and polyproline region heterogeneity were proposed as being associated with viral persistence ( Lhomme et al, 2014 ). Interestingly, our results show that the HEV-3 X domain has several polymorphic amino acids that are associated with clades, an observation that might be consistent with the recently reported clade differences in clinical behavior ( Schemmerer et al, 2022 ). Additionally, it has recently been suggested that the conserved macrodomain is a potential therapeutic target for coronavirus and alphavirus ( Leung et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…Increased HEV prevalence in farm animals and wildlife has been reported in France and other European countries since 2015. Rising HEV incidence has also been documented in blood donors and the general population 39–42 …”
Section: Resultsmentioning
confidence: 98%
“…Rising HEV incidence has also been documented in blood donors and the general population. [39][40][41][42] No cases of TA-GVHD, a potentially fatal reaction associated with donor leucocytes, were reported for any PCs in any period.…”
Section: Trs Of Special Interest (Trsi)mentioning
confidence: 99%
“…HEV genotypes 1 to 4 are further divided into numerous sub-genotypes, with the HEV genotype 3 (HEV-3) sub-genotypes grouped into three monophyletic clades: clade 1 (3e, f, and g), clade 2 (a, b, c, h, i, j, k, l, and m), and HEV-3ra (rabbit) [ 3 ]. Interestingly, the strains from HEV-3 clade 1 were reported to be associated with more severe disease in humans compared with the HEV-3 group 2 strains [ 7 ]. Given its large territory, the Russian Federation is bordered by both non-endemic European countries where HEV-3 is tightly controlled [ 8 ], and endemic territories, such as the Central Asian countries and China, where both the zoonotic genotypes 3 and 4, as well as the anthroponotic genotype 1, are prevalent [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%